2023
DOI: 10.3390/horticulturae9060723
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Tools for the Nitrogen Fertilization Traceability of Organic Farming Products

Abstract: In the last decades, consumers have become increasingly interested in organic products, and they strongly demand reliability in the traceability of the organic products they buy and eat. Several research methods have been developed in the last decades to study inexperienced and reliable systems and to assess the authenticity of products obtained using organic cultivation practices. The monitoring of some chemical compounds, originating from primary and/or secondary metabolism, in horticultural organic and conv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In addition, there is evidence that insects have a lower preference for organically fertilized (OF) plants. Organic fertilization has recently gained importance because it shows less nutrient loss and is more environmentally friendly than conventional fertilization (CF) [10]. In line with the above, it has been reported that the type of fertilization used affects plant chemical compounds [11,12].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, there is evidence that insects have a lower preference for organically fertilized (OF) plants. Organic fertilization has recently gained importance because it shows less nutrient loss and is more environmentally friendly than conventional fertilization (CF) [10]. In line with the above, it has been reported that the type of fertilization used affects plant chemical compounds [11,12].…”
Section: Introductionmentioning
confidence: 87%
“…The nitrogen fertilization traceability in organic products still remains a matter of great relevance and interest, since synthetic mineral fertilizers are not allowed in organic cultivation, and the need to identify their fraudulent use is pressing. Very recently, an integrated approach has been proposed to evaluate the authenticity of organic produces using isotopic data and other chemical and biological parameters alongside the use of chemometrics [29]. However, at the moment, there is still a lack of knowledge regarding how these new methodologies can be applied in specific and different productive and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A key difference between organic and conventional crop cultivation is whether the applied nutrients are derived from organic or chemical fertilizers [17,18]. Studies have shown that the δ 15 N values of chemical fertilizers are close to air (~0‰), while the δ 15 N values of organic fertilizers from different sources are between +0.6‰ and 16.2‰ [19][20][21]. The fertilizers commonly applied in China during organic tea cultivation include organic plant fertilizers such as rapeseed cake, and animal wastes such as chicken, pig, or cow manure.…”
Section: Introductionmentioning
confidence: 99%